(untitled) (Eduscotech, 2019)
This research is to find out the physical fitness level of visitors 10-12 years old SDN Teguhan 02 Jiwan, Madiun. This research is a study that uses a survey method. The subject of this research is the Extracurricular Students of SDN Teguhan 02 Jiwan, with a total of 35 students. Data collection techniques use the TKJI instrument in 2010 for children aged 10-12 years. Data analysis techniques in this study are descriptive statistical analysis with percentages. The results showed 30 students (85.71%) had less physical condition, 4 students (14.28%) had moderate physical condition. It can be concluded that the level of physical fitness in students of SDN Teguhan 02 Jiwan Football Extracurricular is mostly in the less category.